Assessment of the relationship between the educational environment and academic performance of undergraduate medical students of Azad Kashmir - Arslaan Javaeed; Khola Ishtiaq; Aroosa Nawaz; Shafqat Husnain Khan; Zerlishat Shabbir; Sanniya Khan Ghauri (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the relationship between the educational environment and academic performance of undergraduate medical students of Azad Kashmir. Methodology: A cross-sectional study was done, including 324 undergraduate medical students. The study was conducted from September 2018 to September 2019 at Poonch Medical College, Rawalakot, Azad Kashmir. Dundee Ready Education Environment Measure questionnaire was used as the data collection tool. It is a 50 five-point Likert scale questionnaire divided into five domains that identify issues in learning environments. It was distributed electronically to all 500 students, out of them, 324 completed and returned (response rate of 64.8%). Results: The mean Dundee Ready Education Environment score, teaching view of learners score, teacher view of learners score, scholarly self-perception of learners score, atmospheric perception of learners, and cultural self-perception of learners scores for all respondents were 96.31 ± 18.47, 27.85 ± 6.80, 25.13 ± 5.90, 21.10 ± 4.44, 27.47 ± 6.60, and 15.98 ± 3.69 respectively. The Dundee Ready Education Environment score was not significantly correlated with academic performance. The subdomain mean scores were also not significantly correlated with academic performance. However, weak correlations between some of the specific items of the questionnaire and academic performance were observed. Academic performance was significantly higher among females (p .002).